Respuesta :

Step-by-step explanation:

[tex] \tan(2x) = 1.5[/tex]

Take the arc tangent,

[tex] \tan {}^{ - 1} ( \tan(2x) ) = \tan {}^{ - 1} (1.5) [/tex]

[tex]2x = 56.3[/tex]

[tex]x = 28.15[/tex]

b.

[tex](3 \cos(x) + 1)(2 \cos(x) + 3) = - 2[/tex]

[tex]6 \cos {}^{2} (x) + 11 \cos(x) + 3 = - 2[/tex]

[tex]6 \cos {}^{2} (x) + 11 \cos(x) + 5 = 0[/tex]

[tex]6 \cos {}^{2} (x) + 6 \cos(x) + 5 \cos(x) + 5 = 0[/tex]

[tex]6 \cos(x) ( \cos(x) + 1) + 5( \cos(x) + 1) = 0[/tex]

[tex](6 \cos(x) + 5)( \cos(x) + 1) = 0[/tex]

Set each factor equal to zero.

[tex]6 \cos(x) + 5 = 0[/tex]

[tex]6 \cos(x) = - 5[/tex]

[tex] \cos(x) = - \frac{5}{6} [/tex]

[tex]x = \cos {}^{ - 1} ( \frac{5}{6} ) [/tex]

[tex]x = 146.4[/tex]

For the second factor,

[tex] \cos(x) + 1 = 0[/tex]

[tex] \cos(x) = - 1[/tex]

[tex]x = 180[/tex]

So the answer for the second one is

146.4 and 180.

ACCESS MORE